2020
DOI: 10.3897/folmed.62.e50200
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Orthodontic Primer Harboring Chitosan Nanoparticles against the Multispecies Biofilm of Cariogenic Bacteria in a Rat Model

Abstract: Introduction: Microbial biofilm accumulation around orthodontic brackets and composite is a common complication of fixed orth-odontic treatment. This study assessed the antibacterial effects of orthodontic primer containing chitosan nanoparticles (CNPs) against the multispecies biofilm of cariogenic bacteria in а rat model. Materials and methods: Transbond XT orthodontic primer containing 0%, 1%, 5%, and 10% CNPs was experimentally prepared. The Wistar rats were randomly divided into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…e result of the study coincided with previous studies that had demonstrated the antibacterial property of Chitosan and nano chitosan particles. [16][17][18][19][20][21][22][23][24] Chitosan exhibited potent antimicrobial properties against cariogenic bacteria when added to dentifrices, mouthwashes, composite resins, orthodontic bonding agents, and impression materials without affecting their mechanical and clinical properties. [16][17][18][19][20][21][22][23][24] Chitosan acts against bacteria by inhibiting the bacterial enzymes, causing chelation of metal ions and forming polyelectrolyte complexes on the bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e result of the study coincided with previous studies that had demonstrated the antibacterial property of Chitosan and nano chitosan particles. [16][17][18][19][20][21][22][23][24] Chitosan exhibited potent antimicrobial properties against cariogenic bacteria when added to dentifrices, mouthwashes, composite resins, orthodontic bonding agents, and impression materials without affecting their mechanical and clinical properties. [16][17][18][19][20][21][22][23][24] Chitosan acts against bacteria by inhibiting the bacterial enzymes, causing chelation of metal ions and forming polyelectrolyte complexes on the bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Chitosan exhibited potent antimicrobial properties against cariogenic bacteria when added to dentifrices, mouthwashes, composite resins, orthodontic bonding agents, and impression materials without affecting their mechanical and clinical properties. [16][17][18][19][20][21][22][23][24] Chitosan acts against bacteria by inhibiting the bacterial enzymes, causing chelation of metal ions and forming polyelectrolyte complexes on the bacterial cell wall. [17,[25][26][27][28][29][30] is specific action of chitosan against S. mutans and L. acidophilus may be due to the presence of more anionic peptidoglycan and Teichoic acid in the cell wall of gram-positive bacteria that interact with the cationic amino group of chitosan leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The standardization of drops is achieved by using a 10–100 µ m sampler (Cypress Diagnostics, Hulshout, Belgium). The addition and mixing procedures were conducted in a semidark room [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan is a naturally produced biopolymer which is created via deacetylation of chitin [ 12 ]. Chitosan and its derivatives have piqued the interest of researchers due to its ability to reduce Streptococcus mutans , Streptococcus sanguinis , and fungi [ 13 ]. This polysaccharide-based polymer offers nontoxic, biodegradable and biocompatible properties that can be used to replace the limits of metal nanoparticles [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rats were anesthetized with an intramuscular injection of a combination of 6 mg/kg xylazine hydrochloride and 50 mg/kg ketamine hydrochloride (both from Syntec, Santana de Parnaiba, Sao Paulo, Brazil) [ 43 ] before placement of orthodontic appliances. At the end of the experimental period, the animals were euthanized with an overdose of ketamine and xylazine, and sacrificed and their maxilla was resected.…”
Section: Methodsmentioning
confidence: 99%